Emotional, physical, and social needs among 0–5‐year‐old children displaced by the 2010 Chilean earthquake: associated characteristics and exposures. Issue 2 (12th May 2016) - Arbour, MaryCatherine; Murray, Kara A.; Yoshikawa, Hirokazu; Arriet, Felipe; Moraga, Cecilia; Vega, Miguel Angel Cordero
Abstract : An 8.8‐magnitude earthquake occurred off the coast of Chile on 27 February 2010, displacing nearly 2, 000 children aged less than five years to emergency housing camps. Nine months later, this study assessed the needs of 140 displaced 0–5‐year‐old children in six domains: caregiver stability and protection; health; housing; nutrition; psychosocial situation; and stimulation. Multivariate regression was applied to examine the degree to which emotional, physical, and social needs were associated with baseline characteristics and exposure to the earthquake, to stressful events, and to ongoing risks in the proximal post‐earthquake context. In each domain, 20 per cent or fewer children had unmet needs. Of all children in the sample, 20 per cent had unmet needs in multiple domains. Children's emotional, physical, and social needs were associated with ongoing exposures amenable to intervention, more than with baseline characteristics or epicentre proximity. Relief efforts should address multiple interrelated domains of child well‐being and ongoing risks in post‐disaster settings.